Pelatihan Konten Marketing dan Live Tiktok Untuk Pendidikan Kewirausahaan Berkualitas SMK Al Wathoniyah - Menati Fajar Rizki; Indah Fajar Rosalina; Anggun Nadia Fatimah (Bumi: Jurnal Hasil Kegiatan Sosialisasi Pengabdian kepada Masyarakat, 2026)
This community service activity was conducted in response to challenges faced by the business incubator of Al Wathoniyah Klender Foundation, where participants had already produced a laundry perfume product under the brand Mitra Hasanah but had not yet utilized digital platforms for marketing due to limited knowledge and skills. The program aimed to equip 15 participants, consisting of students and teachers of SMK Al Wathoniyah Klender, with content marketing competencies and live selling skills on TikTok through a sequential approach: introducing the product through content, building a digital presence, and ultimately selling the product through TikTok live streaming. The implementation method comprised four stages: partner needs analysis, content marketing training and TikTok account creation, content production practice and live selling simulation, and program evaluation using a Likert-scale pre-test and post-test. Evaluation results showed an average score increase from 1.46 in the pre-test to 4.47 in the post-test, reflecting a significant improvement in participants' understanding and readiness. This program contributes to strengthening quality entrepreneurship education in alignment with SDGs Goal 4.